Labor and the locavore : the making of a comprehensive food ethic - Gray, Margaret, 1968- (University of California Press, 2014)
In the blizzard of attention around the virtues of local food production, food writers and activists place environmental protection, animal welfare, and saving small farms at the forefront of their attention. Yet amid this turn to wholesome and responsible food choices, the lives and working conditions of farmworkers are often an afterthought. Labor and the Locavore focuses on one of the most vibrant local food economies in the country, the Hudson Valley that supplies New York restaurants and farmers markets. Based on more than a decade's in-depth interviews with workers, farmers, and others, G.